Assessing blockchain potential for improving the cybersecurity of financial transactions. Issue 6 (2nd October 2019) - Smith, Kane J.; Dhillon, Gurpreet
Abstract : Purpose: Blockchain holds promise as a potential solution to the problem of cybersecurity in financial transactions. However, difficulty exists for both the industry and organizations in assessing this potential solution. Hence, it is important to understand how organizations in the financial sector can address these concerns by exploring blockchain implementation for financial transactions in the context of cybersecurity. To do this, the problem question is threefold: first, what objectives are important based on the strategic values of an organization for evaluating cybersecurity to improve the security of financial transactions? Second, how can they be used to ensure the cybersecurity of financial transactions in a financial organization? Third, how can these objectives be used to evaluate blockchain as a potential solution for enhancing the cybersecurity of organizations in the financial sector relative to existing cybersecurity methods? The paper aims to discuss this issue. Design/methodology/approach: To accomplish this goal we utilize Keeney's (1992) multi-objective decision analytics technique, termed value-focused thinking (VFT), to demonstrate how organizations can assess a blockchain solution's value to maximize value-add within financial organization. Findings: The presented model clearly demonstrates the viability of using Keeney's (1992) VFT technique as a multi-criteria decision analysis tool for assessing blockchain technology. Further, a clear explanation of how this model can be extended and adapted for individual organizational use is provided. Originality/value: This paper engages both the academic literature as well as an expert panel to develop an assessment model for blockchain technology related to financial transactions by providing a useful method for structuring the decision-making process of organizations around blockchain technology.